Computational Functions for Defining the Standards of Body Weight for Indian Dromedary Camel - Priyank Vyas; S.C. Mehta; Pallavi Joshi (The Indian Veterinary Journal, 2023)
The precise knowledge of body weight of livestock species helps the stakeholder and planners in deciding the requirements of the animals at specific age for feed, space, medication and others. At times, the stakeholders don’t have appropriate knowledge of weight of the animals and weighing of large animals like camels, may not be feasible. This study was therefore taken up to define the standards of growth of Indian dromedary for birth to 20 years of age. This was followed by a static phase with slight decline towards the later age with average body weight ranging from 598 to 555 kg. The R2 values reflecting the goodness-of-fit obtained were 0.671, 0.946, 0.425, 0.944, 0.990 and 0.466, respectively in linear, logarithmic, inverse, quadratic, cubic and exponential functions. The study concludes that the cubic equationY = 93.982 + 10.213x - 0.06519x2+0.00012932x3 (x is age in months) can be utilized for the prediction of body weight of Indian dromedary. For precision, separate equations for the two sexes were also derived. The predicted values may suitably be used by the stakeholder and planners for better planning and management of the Indian dromedary camel.